Faktor-Faktor yang Memengaruhi Keputusan Pembelian Buku pada Mahasiswa - Sulistyo, Adi; Sumarwan, Ujang; Aminah, Mimin (Jurnal Manajemen, 2021)
Publishers and bookstores declined in book sales from 2013 to 2020. The study aimed to find out factors that caused book sales declined and students influencing factors in buying books. There are various factors that influencing the decision to purchase books, i.e price, product, location, promotion, lifestyle, word of mouth technology, and information. This study used 205 respondents who are students of IPB University. The data collection technique used is Probability sampling, a random sampling method. Sample selection using convenience sampling is a sampling technique from the person or unit that is the easiest to find or access. The sampling done by the interview method and filled out a questionnaire on the google form. PLS SEM test tool used to data analysis. SEM (Structural Equation Models) is a statistical technique that aims to build or test statistical models, which are usually causal This research is a field of consumer behaviour science. The research was conducted on the Bogor Agricultural University campus from December 2020 to April 2021. The author chose the location of this research purposively because the object of the research was active Bogor Agricultural University students The study results showed that the product, price, word of mouth, lifestyle, technology, and information factors had a significant effect on students buying book decisions. Location and promotion factors have no significant effect on students purchase book decisions.